Semagacestat pharmacokinetics are not significantly affected by formulation, food, or time of dosing in healthy participants - Willis, Brian A; Zhang, Wei; Ayan-Oshodi, Mosun; Lowe, Stephen L; Annes, William F; Sirois, Paul J; Friedrich, Stuart; de la Peña, Amparo (Journal of clinical pharmacology, 2012)
Semagacestat, a γ-secretase inhibitor, reduces formation of amyloid beta peptide. Two single-dose (140 mg), open-label, randomized, 3-period, crossover studies evaluated the effect of formulation, food, and time of dosing on the pharmacokinetics and pharmacodynamics of semagacestat in healthy participants. The first study (n = 14) compared tablet to capsules. For all formulations, the median time to maximum plasma concentration (t(max)) was generally 1.0 hour. Plasma elimination was rapid, with a half-life of approximately 2.5 hours. Tablet form II bioavailability (F) relative to capsule was approximately 100% (F = 1.03 [90% confidence interval (CI), 0.96-1.10]). In the second study, participants (n = 27) received semagacestat either fed or fasting in the morning or fasting in the evening. No significant change in exposure (AUC(0-∞) [area under the concentration-time curve from 0 to infinity] ratio = 1.02, [90% CI, 0.990-1.05]) occurred with food, whereas maximum plasma concentration (C(max)) declined approximately 15%, and median t(max) was delayed to 1.5 hours. Time of dosing made no significant difference in AUC(0-∞), C(max), or t(max) (AUC(0-∞) ratio 1.01, [90% CI, 0.975-1.04]). No clinically significant safety concerns occurred in either study. Accordingly, semagacestat may be dosed without regard to formulation, food, or time of administration.